2012
DOI: 10.1161/strokeaha.112.663286
|View full text |Cite
|
Sign up to set email alerts
|

Red Meat Consumption and Risk of Stroke

Abstract: Background and Purpose-Prospective studies of red meat consumption and risk of stroke have provided inconsistent results. We performed a meta-analysis to summarize the evidence regarding the effects of red meat (fresh, processed, and total) consumption on stroke risk. Methods-Studies were identified by searching the PubMed database through May 26, 2012, and by reviewing the reference lists of retrieved articles. Prospective studies that reported relative risks (RR) with 95% confidence intervals (CI) for the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(60 citation statements)
references
References 48 publications
(47 reference statements)
1
58
0
1
Order By: Relevance
“…Because the large sample size increased the likelihood of significant findings, a result concerning mean intake was interpreted as significant if it had a P value of <0·002 and if the difference in mean intake between individuals in the highest SEP category and those in the lowest category was clinically relevant. Based on results of meta-analyses on the effects of AF intake on cancers and CVD (1,4,(36)(37)(38) , the difference in intake of red meat, processed meat, poultry, fish, eggs and cheese was considered significant if it was >5 g/d. The difference in milk intake was interpreted as significant if it was >20 g/d, while the threshold was 12 g/d for yoghurt and cream dessert intake.…”
Section: Discussionmentioning
confidence: 99%
“…Because the large sample size increased the likelihood of significant findings, a result concerning mean intake was interpreted as significant if it had a P value of <0·002 and if the difference in mean intake between individuals in the highest SEP category and those in the lowest category was clinically relevant. Based on results of meta-analyses on the effects of AF intake on cancers and CVD (1,4,(36)(37)(38) , the difference in intake of red meat, processed meat, poultry, fish, eggs and cheese was considered significant if it was >5 g/d. The difference in milk intake was interpreted as significant if it was >20 g/d, while the threshold was 12 g/d for yoghurt and cream dessert intake.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus remarkable that the highest levels of choline and L-carnitine are often found in foods rich in cholesterol and fats, such as red meat, liver, and egg yolk. While numerous large-scale epidemiologic studies have linked red meat ingestion with heightened mortality and CVD risks, the relationship between egg ingestion and cardiovascular risks has shown conflicting results (40)(41)(42)(43)(44)(45)(46)(47)(48)(49). Since other dietary nutrients possess a TMA moiety (e.g., glycerophosphocholine, betaine, various short-and long-chain acyl carnitines, and sphingomyelin), there are likely other gut microbe-dependent pathways that lead to the formation of TMA and TMAO, though these remain largely unexplored.…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 99%
“…Loss-adjusted food availability data from 2012 indicate that the average per capita consumption of red meat (processed and unprocessed) is 3·1 oz/d (88·5 g/d) or 53 % of the total meat intake; while NHANES 2011-2012 data indicate that the US consumption is 1·6 oz/capita per d (44·2 g/d) for unprocessed red meat (35 % of the total meat; data on total red meat are not available) and 1·0 oz/capita per d (27·8 g/d) for processed meat (red meat and poultry; 22 % of the total meat). Epidemiological studies have illuminated the increased health risks associated with red and processed meat consumption (2,3,(5)(6)(7)(8)(9)(10) , along with the decreased health risks associated with replacing red meat for equal servings of poultry, fish and plant-based foods (1,4,46) . With this preponderance of evidence, the 2015 Dietary Guidelines Advisory Committee most recently recommended reducing intake of red and processed meat in favour of plant-based alternatives in its scientific report released in February 2015 (23) .…”
Section: Data Comparisons To Dietary Recommendationsmentioning
confidence: 99%
“…An increasing number of epidemiological studies have shown a connection between meat consumption (especially red and processed meat) and health problems such as heart disease (1,2) , stroke (3) , diabetes (4,5) , obesity (6) and certain cancers (1,2,(7)(8)(9)(10) . Environmental scientists have implicated meat production, particularly industrial animal production systems, in contributing significantly to greenhouse gas emissions, climate change, and resource depletion and pollution (11) .…”
mentioning
confidence: 99%